The Creation Process of Gajah Barong Dance at Lingga Purbasari Studio, Baregbeg, Ciamis - Mohammad Rizky Setiaji; Ayo Sunaryo; Saian Badaruddin (Melayu Arts and Performance Journal, 2026)
This study aims to describe and analyze the creation process of the Gajah Barong Dance at the Lingga Purbasari Studio in Baregbeg District, Ciamis Regency, as a form of reinterpretation of local culture based on the myth of the Gajah Barong Site. This research employed a qualitative approach with participatory ethnography methods through observation, interviews, and documentation. The results indicate that the dance creation process proceeded through stages of exploration, improvisation, evaluation, and formation, conducted reflectively and collaboratively. Each element of the performance—movement, music, makeup, costume, and props—integrated to construct a narrative about leadership, spirituality, and life balance. Innovation and artistry were also evident in the use of a hybrid music performance concept using a Digital Audio Workstation (DAW), which enhanced the dramatic atmosphere without losing the identity of Sundanese tradition. The primary contribution of this research lies in documenting the creative process of dance based on local myths and strengthening the ethnochoreological perspective in understanding the relationship between creative practices, embodied experiences, and sociocultural contexts. The research findings demonstrate that the preservation of traditional arts can be achieved through a creative and adaptive approach to contemporary developments without losing their underlying philosophical and cultural values.